Censurae Librorum - The Power to Inspire: Classical Antiquity and Modern Imagination - Olechowska, Elżbieta (Polskie Towarzystwo Filologiczne, 2019)
Zawiera mówienie i recenzje prac: Brett M. Rogers, Benjamin Eldon Stevens (eds.), Classical Traditions in Modern Fantasy, New York: Oxford University Press, 2017, X, 367 pp., ISBN 978-0-1906-1006-7 (pbk.), £86.00(hb.)/29.49 (pbk.).Jesse Weiner, Benjamin Eldon Stevens, Bret M. Rogers (eds.), Frankenstein and Its Classics.The Modern Prometheus from Antiquity to Science Fiction, London: Bloomsbury Academic, 2018 (Bloomsbury Studies in Classical Reception), XII, 233 pp., ISBN 978-1-3500-5487-5 (pbk.), £65.00(hb.)/21.00 (pbk.). Brett M. Rogers, Benjamin Eldon Stevens (eds.), Once and Future Antiquities in Science Fiction and Fantasy, London: Bloomsbury Academic, 2019 (Bloomsbury Studies in Classical Reception), XIV, 273 pp., ISBN 978-1-3500-7488-0 (pbk.), £65.00 (hb.)/19.99 (pbk.).